Spectrum of presentation of pregnancy induced hypertension with maternal and perinatal outcomes at a tertiary care centre - Paul, Satarupa; Parashar, Hemlata; Upadhyay, Ankita; Srivastava, Kriti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Hypertension poses a significant threat to a pregnant woman and many times leads to unfavourable perinatal outcomes with untoward complications. It can also lead to future cardiovascular risk for mothers. This retrospective study was undertaken to assess the different types of hypertensive disorders in pregnancy and the associated neonatal outcomes. Methods: It was a retrospective study conducted for 3 years (January 2019-December 2021) in the department of Obstetrics and Gynaecology at Chirayu Medical College and hospital, Bhopal. A total of 149 women with hypertensive disorders of pregnancy were enrolled in this study as per inclusion-exclusion criteria. Study recorded the type of hypertensive disorder, clinical presentation, laboratory parameters, management with perinatal outcomes using preformed proforma. Data was entered and analyzed by MS excel sheet with the help of Epi Info (TM) 7.2.2.2. Results: In this study, most patients were in the age group of 26-30 years (36.9%) and more patients were multiparous (55.7%). Edema was the predominant symptom (32.9%). Among the enrolled pregnancy induced hypertensive (PIH) patients, 9.3% developed complications with ante partum haemorrhage (APH) being the most common (4%). Severe hypertension seen in 26.8% patients. Also 28.2% patients received anticonvulsant while antihypertensives were given to 43% patients. The most common hypertensive disorder was gestational hypertension (55.7%) followed by preeclampsia (29.5%). Preterm delivery occurred in 39.6% patients while intra uterine growth restriction (IUGR) seen in 18.1% babies. Conclusions: Hypertensive disorders in pregnancy lead to multiple adverse feto-maternal outcomes. In this study most mothers had gestational hypertension while prematurity and low birth weight were common foetal outcomes. Hence early recognition with suitable medical management and follow up of patients would lead to favourable outcomes in PIH.